Purple corn extract (PCE) alleviates cigarette smoke (CS)-induced DNA damage in rodent blood cells by activation of AMPK/Foxo3a/MnSOD pathway - Wan-Sik Kim; Chea-Ha Kim; Jung-Min Lee; Jeong-Ho Jeon; Beom-Goo Kang; Madhuri Shende Warkad; Gozde Inci; Hong-Won Suh; Soon Sung Lim; Sung-Chan Kim; Jaebong Kim; Jae-Yong Lee (Animal Cells and Systems, 2021)
Purple corn extract (PCE) is a nutraceutical, an activator of AMPK, and it has antioxidants and anticancer properties. Therefore, PCE could be a candidate for alleviating cigarette smoke (CS)-induced oxidative DNA damage. This study examined whether PCE can have a protective effect on blood cells in an animal model of cigarette smoke (CS)-induced DNA damage. PCE was orally administered to CS-inhaled Spraque-Dawley (SD) rats, followed by the target cells being examined for markers of DNA damage. The study also sought to elucidate the mechanism of PCE action in the PCE treated animals. SD rat inhalation of CS was for once a day for 30 min, repeated for 7 days. PCE was administered orally before CS inhalation. Pretreatment of the animals with oral PCE kept the numbers of white blood cells (WBC) as well as neutrophils (NE), lymphocytes (LY), monocytes (Mo), eosinophils (EO), abd jasophils (BA) from increasing as those were increased in the CS-inhaling SD rats. The amount of phosphorylated γ-H2AX, a DNA damage marker, was assayed in the circulating blood cells collected from the animals and western blot analysis with anti-Foxo3a, p-Foxo3a, p-AMPK, MnSOD antibodies were performed on those cells. PCE protected the circulating blood cells from CS inhalation-induced DNA damage by 44% as assayed by increases in γ-H2AX. PCE also increased the nuclear localization of Foxo3a by 52% over control cells. Mechanistically, PCE appears to efficiently protect various blood cell types from CS-induced DNA damage through removal of ROS via activation of the AMPK/Foxo3a/MnSOD pathway.